2010
DOI: 10.1111/j.1349-7006.2010.01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive advantage of a cell type classification for pulmonary adenocarcinoma coupled with data for p53, K‐ras and EGFR alterations

Abstract: We analyzed relationships between histological subtypes of pulmonary adenocarcinomas and three gene alterations (p53, K-ras, and epidermal growth factor receptor gene), or thyroid transcription factor-1 (TTF-1) expression, and also studied prognoses by the subtypes, with or without combined multiple gene mutation status. Our purpose was to clearly determine pathogenesis, along with the best predictive value for biology and therapy-related traits. A total of 223 consecutively resected pulmonary adenocarcinomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, mutations of the RB gene are common in small cell cancers but rare in non small lung cell cancers (NSCLC), whereas mutations (or methylation) of P16 are characteristic in the non-small cell cancers [1]. Among NSCLCs, coding mutations of the KRAS and EGFR genes are relatively restricted to adenocarcinoma [2], with EGFR mutations being particular prevalent in adenocarcinoma tumors with the bronchioalveolar histological pattern of growth [3]. Thus, genomic data for lung cancer cannot be generalized across various histological types of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutations of the RB gene are common in small cell cancers but rare in non small lung cell cancers (NSCLC), whereas mutations (or methylation) of P16 are characteristic in the non-small cell cancers [1]. Among NSCLCs, coding mutations of the KRAS and EGFR genes are relatively restricted to adenocarcinoma [2], with EGFR mutations being particular prevalent in adenocarcinoma tumors with the bronchioalveolar histological pattern of growth [3]. Thus, genomic data for lung cancer cannot be generalized across various histological types of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the polygonal cell type was the commonest, the cuboidal cell type was significantly associated with EGFR mutations. A similar study by Okada et al [23] proposed the five-cell type classification and found the hobnail cell type to be significantly associated with EGFR mutations (p<0.001), followed by mixed, columnar/ cuboidal, polygonal and goblet cells. The study also found a higher percentage of smokers to be significantly associated with the cuboidal/ columnar and polygonal cell type, similar to findings in this study where the polygonal cell type was associated with smokers.…”
Section: Discussionmentioning
confidence: 94%